Executive Function Profiles of Kindergarteners and First Graders at Risk for Emotional and Behavioral Disorders. (April 2023) - Cumming, Michelle M.; Poling, Daniel V.; Qiu, Yuxi; Prykanowski, Debra A.; Lumpkins, Aniva; Daunic, Ann P.; Corbett, Nancy; Smith, Stephen W.
Executive function (EF), a set of neurocognitive processes, is central to students' emotional and behavioral well-being. Despite students with emotional and behavioral disorders (EBD) being at risk for negative long-term outcomes, there is a paucity of EF research with students at risk for EBD in early elementary school, an important identification and intervention period. Thus, we conducted a cross-sectional latent profile analysis with a sample of 1, 154 kindergarteners and first graders identified as at risk for EBD to determine whether unique EF profiles existed and the extent to which profile membership was related to distinct patterns of functioning. Results indicated a theoretically supported, three-profile solution of mildly, moderately, and clinically at-risk EF profiles. Differences between EF profiles were noted such that students with moderately and clinically at-risk EF profiles demonstrated more problematic behaviors, less social competence, and greater language difficulties. We discuss implications for early identification, intervention efforts, and future research.